THE ROLE AND POTENTIAL OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN MODERNIZING EDUCATIONAL PROCESSES - Salimova Sarvinoz Farxodovna; Maxmudova Mehriniso Maqsudovna (Web of Journals Publishing, 2025)
This article analyzes the necessity of modernizing the education system in the contemporary world and examines the role and opportunities presented by Information and Communication Technologies (ICT) in this process. It argues that traditional educational methods are proving insufficient amidst the challenges of the 21st century, globalization, and the transition to a digital economy. Conversely, ICT offers extensive possibilities for individualizing education, enhancing interactivity, disseminating knowledge widely, and implementing new pedagogical approaches. The article systematically highlights the role of ICT in improving educational quality, expanding access to resources, and developing students' digital literacy and 21st-century skills. Furthermore, it addresses the main challenges associated with the successful integration of ICT into education and provides recommendations for overcoming them.
Keywords: Information and Communication Technologies (ICT), modernization of education, digital transformation, pedagogical innovations, individual learning trajectories, digital literacy, 21st-century skills, online education, blended learning.